Genetic resources and genomics for adaptation of livestock to climate change - Hoffmann, I.; Baumung, R.; Drucker, Adam G.; McManus, C.; Berg, P.; Stella, A.; Nilsen, L.B.; Moran, D.; Naves, M.; Thompson, M.C. (Frontiers Media, 2015)
Animal genetic resources (AnGR) are critical for global food security and livelihoods. Livestock products have high densities of energy, protein, and other critical nutrients, which are particularly beneficial for infants and expectant mothers. Around a billion people rely directly on livestock for their livelihoods, many of which are among the rural poor (FAO, 2009). Demand for animal products is foreseen to increase significantly in the future while competition for resources will intensify, dictating that livestock systems must increase both productivity and efficiency. Maintaining sufficient diversity of AnGR is necessary to ensure adaptation potential in times of uncertainty. In the future, climate change is expected to be a major force testing resilience of global food production systems (Thornton et al., 2009; Renaudeau et al., 2012). Ensuring that livestock systems remain productive and efficient while maintaining their flexibility will be a major challenge.